A DEEP INSIGHT INTO ZAHID AL-KAWTHARI AND HIS SCHOLARLY ACTIVITY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the life and scholarly contributions of Zahid al-Kawthari, a prominent figure of Islamic scholarship in the last century. A significant portion of al-Kawthari’s intellectual legacy is dedicated to writing refutations against the rising trend of anti-madhhab (non-school-based) ideologies that were gradually spreading in certain regions during his time. In addition to this, the scholar was also actively engaged in various other branches of Islamic sciences, leaving a lasting impact through his multifaceted academic work.